2002
DOI: 10.1002/app.10475
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and mechanical properties of unidirectional sisal– epoxy composites

Abstract: Plant fibers are of increasing interest for use in composite materials. They are renewable resources and waste management is easier than with glass fibers. In the present study, longitudinal stiffness and strength as well as morphology of unidirectional sisal-epoxy composites manufactured by resin transfer molding (RTM) were studied. Horseshoe-shaped sisal fiber bundles (technical fibers) were nonuniformly distributed in the matrix. In contrast to many wood composites, lumen was not filled by polymer matrix. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(80 citation statements)
references
References 14 publications
2
73
0
Order By: Relevance
“…The volume fraction has a critical effect on the properties of natural fibre bio-composites. A value between 30-40% has been used in numerous studies and was proven to give natural fibre composites of high quality and thermo-mechanical properties [2,3,14,21,24]. It was observed that the properties will generally improve with an increased volume fraction, up to a certain value, after which further increase result in weaker components.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The volume fraction has a critical effect on the properties of natural fibre bio-composites. A value between 30-40% has been used in numerous studies and was proven to give natural fibre composites of high quality and thermo-mechanical properties [2,3,14,21,24]. It was observed that the properties will generally improve with an increased volume fraction, up to a certain value, after which further increase result in weaker components.…”
Section: Methodsmentioning
confidence: 99%
“…Epoxy resins are also very commonly selected from the automotive industry [1] for the manufacturing of natural fibre biocomposites, and are among the most studied resins to be combined with natural fibres [24] in the literature. Further, there is today a wide range of available bio-sourced epoxy resins (extracted from natural sources such as epoxidised vegetables oils (EVOs) like pine oil waste and soya oil, or waste streams of other industrial processes, such as wood pulp and bio-fuels production) in the European market and an increasing number of companies with extended knowledge on the production of natural composites using these resins.…”
Section: Methodsmentioning
confidence: 99%
“…The fiber volume fraction (V f ) is an important parameter in the theoretical calculations for strength, modulus, and other properties of fiberreinforced composite materials and it can be calculated using the following equation [17]:…”
Section: Determination Of the Fiber Volume Fraction (V F )mentioning
confidence: 99%
“…The potential of using agricultural waste, such as sisal, jute, pineapple leaves, banana stems, oil palm, rice hulls and sugar palm as fillers is being explored. These biomass residues are all mostly available in abundance, can be obtained for little or no cost and are renewable throughout the whole year in countries like Malaysia (Oksman, Wallström, Berglund, & Romildo, 2002;Arib, Sapuan, Ahmad, Tahir, & Dahlan, 2006;Foo & Hameed, 2009;Zainudin, Sapuan, Abdan, & Mohamad, 2009;Hisham, Faieza, Ismail, Sapuan, & Ibrahim, 2011;Ishak, Sapuan, Leman, Rahman, & Anwar, 2011). Of all these residues, only a small proportion are used as household fuel or fertilisers and the remainder are considered as waste, which poses a negative effect for the environment (Chaudhary, 2004).…”
Section: Introductionmentioning
confidence: 99%